THE INTRODUCTION OF PROBLEM-BASED LEARNING METHODS INTO THE PRACTICE OF A PHYSICS TEACHER AND THE STUDY OF THE EFFECTIVENESS OF THEIR USE IN THE DEVELOPMENT OF STUDENTS' RESEARCH SKILLS - Tastanov, M.G.; Tuktubayeva, S.A. (Publisher of Kostanay Regional University named after Akhmet Baityrsynuly, 2024)
This article examines the introduction of problem-based learning (PBL) into physics teaching and analyzes its effectiveness in developing students’ research skills. Problem-based learning encourages involvement of students in the learning process, development of critical thinking, independence, and teamwork skills. Special emphasis is placed on practical experiments and real-world scenario modeling, which helps students better understand theoretical material and apply it in practice. The study results include survey data, academic performance, and project task completion among students, confirming the positive impact of PBL on the learning process. The article also provides recommendations for further integrating PBL into the school curriculum and for teacher professional development to support more effective application of this method.
Keywords: problematic issue; problem-based learning (PBL) methods; research skills; simulation of laboratory experiments